Euthyroid pretibial myxedema and EMO syndrome - Şenel, Engin (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
EMO syndrome is a rare extrathyroid syndrome, seen in only 1% of patients affected by extrathyroid complications of Graves' disease. A 73-year-old womanpresented with a 1-year history of asymptomatic local swellings on her legs and feet. Physical examination revealed moderate proptosis and multiple, firm subcutaneous nodules of 1 to 5 cm in diameter located on the anterior andmedial aspects of the shins and on feet. The patient had a history of bilateral knee arthroplasty 5 years ago. Histopathologic examination showed deposition of mucin and perivascular lymphocytic infiltration in the dermis. Dermatologic and pathologic findings were consistent with pretibial myxedema. Laboratory tests showed normal thyroid stimulating hormone (TSH) and serum free T3 and T4 levels. The TSH receptor antibody titer was elevated. Thus, with all these findings she was diagnosed with exophthalmia, myxedema, and hypertrophic osteoarthropathy (EMO) syndrome. The lesions were completely treated with three monthly intralesional corticosteroid injections and at the 4-month follow-up no recurrence was observed. Only three euthyroid cases with pretibial myxedema have been reported in the literature. Patients that have asymptomatic pretibial nodular or plaque lesions should be investigated with an ophthalmologic examination and laboratory workup to clarify a possible underlying thyroid gland disease and EMO syndrome.
Keywords: Aged; Etiology; Euthyroid Sick Syndromes; Evtiroidna bolezen, sindromi; Leg Dermatoses; Miksedem; Myxedema; Noga, dermatoze; Pathology; Starostniki; Therapy